Pendampingan dan Edukasi Penyampaian SPT Tahunan Secara Elektronik pada SMP Xaverius 3 Bandar Lampung - Victoria Ari Palma Akadiati; Agnes Susana Merry Purwati; Imelda Sinaga (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Assistance and education in the electronic submission of Annual SPT is a Community Service (PKM) activity which is also the goal of community service activities. Based on the results of survey, interview, and analysis, it can be concluded and identified the experience problem by Partners from the STIE Gentiaras were : 1) the lack of understanding of the electronic submission of Annual SPT, 2) limited knowledge of how to resolve if there was a failure in submitting the Annual Tax Return electronically, 3) there were still participants in community service activities, namely Individual Taxpayers who have a TIN with an inactive EFIN. The method used in community service activities held on March 29, 2022, was carried out through several stages, namely 1) preparation stage, 2) the implementation stage, 3) monitoring stage 4) the evaluation stage. The results obtained in this community service activity are as many as 24 participants consisting of teachers and employees of SMP Xaverius 3 Bandar Lampung can know how to fill out and report the Annual Tax Return of Individual Taxpayers and can practice it directly electronically.